A reusable business tier component with a single wide range static interface - Pereira, Óscar M. (2011)
This research proposes an architecture for reusable components aimed at bridging the object-oriented and the relational paradigms. The component, referred to here as Business Tier Component, provides a single wide range static interface able to manage a set of Create, Read, Update and Delete (CRUD) expressions, deployed at runtime and of any complexity, on behalf of application tiers. The only constraint is that the required interface to manage each CRUD expression must be a super-interface of the provided wide range interface. The main research challenge of this paper is the definition of an architecture for reusable components aimed at managing dynamically a set of CRUD expressions, deployed at runtime, on behalf of application tiers.